The Analysis of Factors Associated with Bronchopneumonia in Children Aged 1-5 Years - Arik Chistiyana Wardani; Umi Kalsum; Rus Andraimi (Formosa Journal of Science and Technology, 2023)
Children under five must receive protection to prevent diseases that can disrupt growth and development or even cause death. One of the diseases that attacks children is bronchopneumonia. Bronchopneumonia can also be triggered by several risk factors that increase morbidity and mortality. Pneumonia is divided into two major groups: intrinsic factors and extrinsic factors. This study aims to determine the factors associated with the incidence of bronchopneumonia in children aged 1–5 years at RSUD dr. Abdul Rivai Berau. This research is a quantitative study using observational analytic methods with a Cross Sectional Study design. There is a relationship between the results of statistical tests showing that there is a relationship between the economy, immunization, exclusive breastfeeding, air pollution, house ventilation and knowledge with Bronchopneumonia, while occupancy density has no relationship with Bronchopneumonia in Children.